The worldwide transformation of higher education - Baker, David, 1952 Jan. 5-; Wiseman, Alexander W., 1968- (International perspectives on education and society ;, 2008)
Higher education worldwide, including the university and other related academic programs, is currently undergoing intensive change and transformation perhaps as no other time in its long history. One factor contributing to this rapid transformation is the global expansion of higher education at unprecedented rates. More of the world's population is continuing to higher education (and other forms of tertiary education) now than ever before. In fact, enrollment in institutions of higher education around the world is growing at a rapid rate. Some scholars have suggested that one reason for this rapid expansion is that the role of higher education has shifted over the last 50 years from an elite to a mass institution. As a result of this rapid expansion and shift in focus, the nature of students, faculty, the curriculum, and assessment is changing within the institution. And in society, the value of higher education and its impact on socioeconomic status, human capital, and technical innovation is changing as well. As a whole, the chapters in this volume in the "International Perspectives on Education and Society" series present a thoughtful discussion of the worldwide transformation of higher education from multiple perspectives. Contributors include Gaele Goastellec, David Turner, John C. Weidman, Adiya Enkhjargal, Christine Min Wotipka, Francisco O. Ramirez, Karin Amos, Lucia Bruno, Marcelo Parreira do Amaral, Mark S. Johnson, Christopher Collins, Robert A. Rhoads, Sunwoong Kim, Jun Li, Jing Lin, Chuing Prudence Chou, Philip G. Altbach, and Patti McGill Peterson.